Omega-3 and Cognition in Children with Malnutrition - Portillo Reyes, Veronica (Elsevier, 2019)
Specific nutrients are critical during different developmental epochs and for specific cellu- lar mechanisms which underlie brain development and cognitive functioning. One nutrient of significant importance to both development and day-to-day functioning is omega-3 fatty acids. The following chapter reviews the specifics of how malnutrition in children can impact development and cognitive performance. Details are provided on the specific influence of both undernutrition and overweight/obesity on cognitive performance. Moreover, the bulk of the following specifically highlights the empirical evidence demonstrating the effect that Omega-3 fatty acid consumption or supplementation has on cognition and neuropsycholog- ical performance in children with malnutrition.